2020
DOI: 10.21203/rs.2.23773/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain morphologic abnormalities in migraine patients: an observational study

Abstract: Background: Migraine is a common neurological disorder characterized by a complex physiopathology. We assessed brain morphologic differences in migraine and the possible pathogenetic mechanism underlying this disease.Methods: We analyzed brain morphologic images of migraine patients, 14 with aura (MwA) [the mean (SD) age was 42.36 (2.95) years (range, 37-47)] and 14 without aura (MwoA) [the mean (SD) age was 43.5 (3.25) years (range, 39-50)] during episodic attack compared with health subjects balanced (HS) [… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(25 reference statements)
1
1
0
Order By: Relevance
“…The research has also shown that the results of the SHAP plot and subgroup analysis are similar, both indicating that the PoCG and INS play a pivotal role in the prediction models. In recent studies using restingstate functional and structural MRI, various brain networks with functional and structural changes have been reported in patients with migraine, and show notable correlations with the clinical features [57,58]. These brain networks are consistent with the brain regions observed in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The research has also shown that the results of the SHAP plot and subgroup analysis are similar, both indicating that the PoCG and INS play a pivotal role in the prediction models. In recent studies using restingstate functional and structural MRI, various brain networks with functional and structural changes have been reported in patients with migraine, and show notable correlations with the clinical features [57,58]. These brain networks are consistent with the brain regions observed in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, an arterial spin labeling study showed that NSAIDs achieved analgesia by inhibiting neural activity in the brain regions of the descending pain regulatory pathway [20]. In addition, patients with migraine experience a loss of volume in the left somatosensory cortex [57], suggesting larger volume of the left S1 positively contributes to predicting therapeutic outcomes, indicating a compensatory mechanism for responding to pain signals [65]. Based on our findings, we inferred that the altered functional and structural characterizations of brain regions in the descending pain regulatory pathway were involved in the neural mechanism of migraine progression and pharmacological treatment.…”
Section: Discussionmentioning
confidence: 99%